PERBANDINGAN KONSTITUSI MADINAH DAN KONSTITUSI AMERIKA SERIKAT DALAM POLITIK KETATANEGARAAN - Duwi Handoko; Rahmad Alamsyah; Hulaimi; Khairul Azwar Anas (LPPM STISIP Persada Bunda, 2022)
Law is a political product if it is understood to be one in this sense, but it can also refer to law in other senses, such as the constitution or the basic law. Therefore, this study poses the question: How were the fundamental articles of the Medina Constitution established at the outset of a nation? What fundamental rules govern a nation at its inception, according to the United States constitution? And what are the parallels and divergences in the constitutional development of the Medina constitution and the US Constitution? This research is of the normative legal research variety. By studying the literature pertinent to the topic of the research, a literature study is employed as the data gathering technique. Based on the definition of the problem, a systematic data analysis was conducted, and the results were qualitatively stated. Declaring the formation of a new ummah to create a new state was one of the fundamental principles of the Medina Constitution at the time the state was established (Islamic State). At the time of the country's establishment, the fundamental clauses of the United States Constitution were already written. The Medina constitution's constitutional growth is comparable to that of the US Constitution in that both are written documents that are always being modified. While the United States constitution does not make any religion the form of its state, the Medina Constitution makes Islam the form of its state.